The methodology of Event History analysis and its application in the quality control of raw milk - Kovács, Sándor (Acta Agraria Debreceniensis, 2006)
Event-history analysis is among the most frequently adopted mathematical methods, mainly due to the numerous types of models, available in the analysis. This method is also appropriate for analysing risk. Specifically, it has been employed in medical and animal-breeding science to manage risks. In this article, I give a presentation of the basic concepts, the basic types of models and their theoretical basis. I deal with the nonparametric Kaplan Meier and the parametric Cox proportional hazard model. The case study is also analysed with these methods. The results shows, that the 16-stall caroussel is the most effective facility from the viewpoint of quality. Milking into assay crucible (sample- cup) is more effective than to the floor after 16 decades.